P-105 Management of a trainee-led research collaborative. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Khiroya, Heena; Freeman, Natasha; Coop, Hazel; Marlow, Clare; Willis, Derek
Abstract : Background: The West Midlands Collaboration Actioning Research in End of life and Supportive Care (WM CARES) is a palliative medicine trainee-led research collaborative, established in 2016. WM CARES enables trainees to be involved in research to benefit patient care and to gain experience in research prior to becoming consultants (Coop, Macfarlane, Twigger, Doré et al ., 2017). Published literature reveals several experiences of setting up trainee-led research collaboratives (Chamberlain, Schofield, Hancock, Etkind et al ., 2019; Dowswell, Bartlett, Futaba, Whisker et al ., 2014) but there is a paucity of information relating to the ongoing management and output of these collaboratives. Existing published work relates mainly to surgical specialties (Dowswell, Bartlett, Futaba, Whisker et al ., 2014; Bhangu, Kolias, Pinkney, Hall et al ., 2013; Jamjoom, Phan, Hutchinson & Kolias, 2016). Aim: This work aims to describe our experience of managing and maintaining a trainee-led research collaborative within the field of palliative medicine. We wanted to understand potential barriers to maintaining a registrar-led research collaborative. Methods: We distributed a survey to the palliative medicine registrars in the West Midlands deanery in March 2019 to explore past, present and future levels of engagement with WM CARES. Results: Fourteen trainees (78% of total) completed the survey. To date, WM CARES has published two papers (Coop & Marlow, 2019; Macfarlane, Shayler, Nelms, Willis et al ., 2018) and the latter has sparked the idea for the first project being conducted by the UK Palliative trainees Research Collaborative (Chamberlain, Schofield, Hancock, Etkind et al ., 2019). Despite the pool of trainees changing since the conception of WM CARES, there is willingness to take on leadership roles within the collaborative, with all roles except one expected to be filled next year. The most common reasons cited for not taking on roles were maternity leave (40%) and completion date of training approaching (30%). Four ideas for future research projects were submitted. Conclusions: Surveying trainees to gauge opinions on our research collaborative has shown a continued enthusiasm for developing research ideas and commitment to trainee-level leadership. WM CARES has demonstrated the value of trainee-led research with an expanding footprint in the palliative care literature.